Impacts of different management systems on the physical quality of an Amazonian Oxisol - Guedes,Elaine Maria Silva (2012)
The physical quality of Amazonian soils is relatively unexplored, due to the unique characteristics of these soils. The index of soil physical quality is a widely accepted measure of the structural quality of soils and has been used to specify the structural quality of some tropical soils, as for example of the Cerrado ecoregion of Brazil. The research objective was to evaluate the physical quality index of an Amazonian dystrophic Oxisol under different management systems. Soils under five managements were sampled in Paragominas, State of Pará: 1) a 20-year-old second-growth forest (Forest); 2) Brachiaria sp pasture; 3) four years of no-tillage (NT4.); 4) eight years of no-tillage (NT8); and 5) two years of conventional tillage (CT2). The soil samples were evaluated for bulk density, macro and microporosity and for soil water retention. The physical quality index of the samples was calculated and the resulting value correlated with soil organic matter, bulk density and porosity. The surface layers of all systems were more compacted than those of the forest. The physical quality of the soil was best represented by the relations of the S index to bulk density and soil organic matter.